Comparison between FLL and PLL in frequency estimation to supply distributed virtual inertia - Novoa, E.; Tafur, J.; Rosas, D.S.Y. (European Association for the Development of Renewable Energy, Environment and Power Quality (EA4EPQ), 2024)
To connect renewable energy sources (e.g. solar or wind) on the grid, an inverter or electronic converter is used. However, a traditional inverter has no inertia in the face of frequency changes. Unlike the inertia of the rotor of a synchronous generator. Frequency variations are a product of the imbalance between the energy generated and the grid loads. If the frequency is too far from its nominal value or if the rate of change of frequency (RoCoF) is high, it can affect the synchronism of the generators that feed the grid. Therefore, power cuts are made in sectors on the grid, thus preventing instability from spreading to other sectors on the grid, which translates into large economic losses. Solutions such as inverters with virtual inertia (or emulated inertia) are a good alternative due to their structural simplicity and low cost, compared to other solutions such as synchronous condensers, for example. For the virtual inertial control strategy, the grid frequency needs to be measured. This article compares the use of a phase-locked loop (PLL) or a frequency-locked loop (FLL) for frequency estimation and its effect on inertia emulation. The proposed control designs are validated through simulations.
Keywords: Virtual inertia; Frequency estimation; Grid-connected inverter; https://purl.org/pe-repo/ocde/ford#2.02.04